2019
DOI: 10.1631/jzus.b1800171
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of herbal medicines for the treatment of cancer cachexia in animal models

Abstract: Objective: The aim of this study is to summarize preclinical studies on herbal medicines used to treat cancer cachexia and its underlying mechanisms. Methods: We searched four representing databases, including PubMed, EMBASE, the Allied and Complementary Medicine Database, and the Web of Science up to December 2016. Randomized animal studies were included if the effects of any herbal medicine were tested on cancer cachexia. The methodological quality was evaluated by the Collaborative Approach to Meta-Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 87 publications
0
16
0
Order By: Relevance
“…More than half of known anticancer drugs originated from herbal plants. Natural products remain one of the best reservoirs for new drug discovery [ 28 ]. Our research group previous extracted myricanol from the bark of M. rubra .…”
Section: Discussionmentioning
confidence: 99%
“…More than half of known anticancer drugs originated from herbal plants. Natural products remain one of the best reservoirs for new drug discovery [ 28 ]. Our research group previous extracted myricanol from the bark of M. rubra .…”
Section: Discussionmentioning
confidence: 99%
“…Among the previous studies, systematic reviews have been conducted on individual cancers [ 42 ], but there has not been a comprehensive study on the five major cancers with high mortality rates worldwide. In addition, the number of research regarding the anti-metastatic effect of herbal medicine is limited and the works are not organized compared to a large number of cancer cachexia studies that have been reported in a wide variety with well-structured forms [ 43 ]. Therefore, we aimed to review the anti-metastatic mechanisms of herbal medicines on five major cancers (lung, colorectal, stomach, liver, and breast).…”
Section: Herbal Medicines and Natural Antioxidantsmentioning
confidence: 99%
“…Cancer trends in young adults, reflect recent changes in carcinogenic exposures, which could foreshadow the future overall disease burden [378]. Cancer cachexia (anorexia, weight loss, loss of adipose tissue and skeletal muscle) is reported in 30%-80% cancer patients and causes 20% of all cancer deaths [379]. Worldwide, some 60%-80% people depend on alternative medicines [380][381][382], which is also true for nearly 40% to 70% European [383,384], 50% Italian, 40% Korean, 30% British [385] and up to 87% of Australian cancer patients [386].…”
Section: Cancer Carementioning
confidence: 99%